Metastatic papillary thyroid carcinoma to the nose: report and review of cutaneous metastases of papillary thyroid cancer - Philip R. Cohen (Mattioli1885, 2015)
Background: Metastatic papillary thyroid carcinoma typically appears in local lymph nodes. Skin metastases are rare. Purpose: A man with progressive metastatic papillary thyroid carcinoma who developed a cutaneous metastasis on his nose is described. The clinical manifestations of metastatic papillary thyroid carcinoma to skin are reviewed. Methods: PubMed was used to search the following terms, separately and in combination: basal, cancer, carcinoma, cell, cutaneous, kinase, inhibitor, metastases, nose, papillary, rearranged during transfection, receptor, RET, thyroid, tyrosine, vandetanib. Results: Pathologic changes observed on the biopsy of the man's nose lesion were similar to those of his original cancer. Genomic evaluation of the tumor revealed an aberration involving the rearranged during transfection (RET) receptor tyrosine kinase. The residual tumor was excised. Treatment with vandetanib, a RET inhibitor was initiated; his metastatic disease has been stable, without symptoms or recurrent cutaneous metastasis, for 2 years following the discovery of his metastatic nose tumor. Conclusions: Papillary thyroid carcinoma with skin metastases is rare. Nodules usually appear on the scalp or neck; the thyroidectomy scar is also a common site. Metastatic tumor, albeit infrequently, can present as a nose lesion. The prognosis for patients with cutaneous metastases from papillary thyroid carcinoma is poor. However, with the ability to test the tumor for genomic aberrations, molecular targeted therapies-such as tyrosine kinase inhibitors-may provide extended survival in these individuals.